The Analisis Problematika Guru dalam Mengintegrasikan Islam pada Pembelajaran Biologi di Madrasah Aliyah Negeri Kabupaten Tanah Datar: Analysis of the Problems Faced by Teachers in Integrating Islam into Biology Learning at State Islamic Senior High Schools in Tanah Datar Regency - Nabilla Darma Nur Zarifah Nabilla; Ardi Ardi (Al-Alam: Islamic Science Education Journal, 2025)
The integration of Islamic values into Biology learning at Madrasah Aliyah is a curricular requirement and a distinctive characteristic of Islamic educational institutions. However, its classroom implementation still faces various challenges. This study aims to analyze the problems encountered by teachers in integrating Islamic values into Biology learning at State Madrasah Aliyah in Tanah Datar Regency. This research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that teachers face challenges such as limited conceptual understanding of Islamic and science integration, difficulties in linking Biology content with Qur’anic verses and Hadith, limited instructional time, lack of integrated teaching materials, and diverse educational backgrounds. Teachers address these challenges by contextualizing Islamic values, engaging in collaborative discussions with colleagues, and utilizing additional learning resources..